2014
DOI: 10.3109/07853890.2014.966752
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of fatty liver in normal-weight and overweight young adults. The Cardiovascular Risk in Young Finns Study

Abstract: Prevalence of fatty liver was 29% in overweight/obese and 5% in normal-weight adults. Differences in factors associated with fatty liver were seen between these two groups: alcohol intake and smoking were more strongly and triglycerides more weakly associated in normal-weight than in overweight/obese participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
56
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 48 publications
3
56
1
Order By: Relevance
“…In addition to risk factors identified in the Cardiovascular Risk in Young Finns Study [11,12], other risk factors are known to be involved. Ethnic background and other genetic factors play a role from birth [5,6].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to risk factors identified in the Cardiovascular Risk in Young Finns Study [11,12], other risk factors are known to be involved. Ethnic background and other genetic factors play a role from birth [5,6].…”
mentioning
confidence: 97%
“…The authors had previously shown that the determinants of fatty liver evaluated at adulthood in the same individuals were waist circumference, alanine aminotransferase, body mass index (BMI), male sex, apolipoprotein B, systolic blood pressure, alcohol intake, insulin and low physical activity index [12]. The highlight of the present study was to consider the genetic background (i.e.…”
mentioning
confidence: 99%
“…Transthoracic echocardiography was performed with Acuson Sequoia 512 (Acuson, Mountain View, CA) ultrasonography, using 3.5 MHz scanning frequency phased-array transducer. 12 The concentration of serum insulin was determined with an immunoassay. Analysis of the echo images was performed by one observer blinded to the clinical details with the CommPACS 10.7.8 (MediMatic Solutions, Genova, Italy) analysis program.…”
Section: Me Thodsmentioning
confidence: 99%
“…All sonographers were trained by a single cardiac imaging specialist. 12 Homeostasis model assessment-estimated insulin resistance (HOMA-IR) was calculated as (insulin × fasting serum glucose)/22.5. 7 We included the study center as a technical covariate in the statistical models to ensure that the results are not driven by differences between the centers.…”
Section: Me Thodsmentioning
confidence: 99%
See 1 more Smart Citation